2013
DOI: 10.1080/00087114.2013.855389
|View full text |Cite
|
Sign up to set email alerts
|

Karyotypes of South American species of the Morelloid and Dulcamaroid clades (Solanum, Solanaceae)

Abstract: A karyotypic study on South American representatives of the Morelloid and Dulcamaroid clades of Solanum was conducted to contribute to a better understanding of their relationships. Mitotic chromosomes of 26 species were examined (13 of which were previously unknown). All taxa presented 2n = 2x = 24 and had small chromosomes (less than 4 μm long) with the exception of S. crispum. Most species displayed symmetrical karyotypes, being 78% and 69% m, 19% and 25% sm and 3% and 6% st for the Morelloid and Dulcamaroi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(31 citation statements)
references
References 36 publications
2
13
0
Order By: Relevance
“…Hybridization with the 18-5.8-26S rDNA probe confirmed the sites of the satellites observed by conventional staining (Moyetta et al 2013) and fluorescent banding techniques reported in this work. This localization suggests a common distribution pattern that occurs in the terminal regions of the chromosomes and is frequent in many angiosperms (e.g.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Hybridization with the 18-5.8-26S rDNA probe confirmed the sites of the satellites observed by conventional staining (Moyetta et al 2013) and fluorescent banding techniques reported in this work. This localization suggests a common distribution pattern that occurs in the terminal regions of the chromosomes and is frequent in many angiosperms (e.g.…”
Section: Discussionsupporting
confidence: 81%
“…In the genus Solanum and in the Morelloid, and Dulcamaroid clades in particular, the cytogenetic knowledge is relatively scanty Acosta et al 2012;Moyetta et al 2013). Most examined species of these clades were karyologically indistinguishable based on conventionally stained mitotic chromosomes (Moyetta et al 2013). Additional molecular karyotype analyses with banding and FISH techniques are needed in both clades to gain a better knowledge of the possible karyoevolutionary trends.…”
Section: Methodsmentioning
confidence: 96%
See 1 more Smart Citation
“…Ploidy level varies from diploid to hexaploid within the group (e.g. Edmonds and Chweya 1997; Moyetta et al 2013; see Table 1), in part contributing to the difficulties in its taxonomy. While taxonomic revisions of the smaller New World sections within the Morelloids have recently been published (del Vitto and Petenatti 1999; Barboza 2003; Barboza and Hunziker 2005), the group in its entirety has not been revised since the 19 th century (Dunal 1852).…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge of CNs in plants is continuously increasing: just in the last year, several studies were published with massive CN data (Chung et al 2013;Dolatyari et al 2013;Kaplan et al 2013;Krahulcova et al 2013;Kuo 2013;Malik and Gupta 2013;Moyetta et al 2013;Ranjbar and Mahmoudi 2013;Wang et al 2013;Zaveska Drabkova 2013;Correia-da-Silva et al 2014;Rani, Jeelani, et al 2014;. The direct insertion of such data in online and constantly updated databases would much benefit the scientific community.…”
Section: Prota4umentioning
confidence: 99%